Theory of Cryptography : 12th Theory of Cryptography Conference, TCC 2015, Warsaw, Poland, March 23-25, 2015, Proceedings, Part I - Dodis, Yevgeniy; Nielsen, Jesper Buus.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2015)
The two-volume set LNCS 9014 and LNCS 9015 constitutes the refereed proceedings of the 12th International Conference on Theory of Cryptography, TCC 2015, held in Warsaw, Poland in March 2015. The 52 revised full papers presented were carefully reviewed and selected from 137 submissions. The papers are organized in topical sections on foundations, symmetric key, multiparty computation, concurrent and resettable security, non-malleable codes and tampering, privacy amplification, encryption an key exchange, pseudorandom functions and applications, proofs and verifiable computation, differential privacy, functional encryption, obfuscation.
Foundations -- Symmetric Key -- Multiparty Computation -- Concurrent and Resettable Security -- Non-malleable Codes and Tampering -- Privacy Amplification -- Encryption and Key Exchange.
Keywords: Data encryption (Computer science).; Computer security; Computer science; Computer software; Computational complexity; Cryptology; Systems and Data Security; Computation by Abstract Devices; Algorithm Analysis and Problem Complexity; Discrete Mathematics in Computer Science